PEMBELAJARANÃÂ KOMPETENSIÃÂ PEMELIHARAANÃÂ DANÃÂ PERBAIKANÃÂ SISTEMÃÂ BAHANÃÂ BAKARÃÂ MENGGUNAKANÃÂ MEDIAÃÂ MEJAÃÂ DANÃÂ WIRINGÃÂ DIAGRAM - TarjuniÃƒÂ‚Ã‚Â , -; AnisÃƒÂ‚Ã‚Â , Samsudin; BudiyonoÃƒÂ‚Ã‚Â , ArisÃƒÂ‚Ã‚Â (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
TujuanÃÂ penelitianÃÂ iniÃÂ adalahÃÂ untukÃÂ mengetahuiÃÂ perbedaanÃÂ kompetensiÃÂ pemeliharaanÃÂ danÃÂ perbaikanÃÂ sistemÃÂ bahanÃÂ bakarÃÂ mesinÃÂ dieselÃÂ padaÃÂ siswaÃÂ tingkatÃÂ XIÃÂ SMKÃÂ IslamÃÂ PemalangÃÂ tahunÃÂ diklatÃÂ 2008/2009ÃÂ denganÃÂ menggunakanÃÂ duaÃÂ mediaÃÂ pembelajaranÃÂ berbedaÃÂ yaituÃÂ mediaÃÂ mejaÃÂ danÃÂ wiringÃÂ diagramÃÂ sistemÃÂ pemanasanÃÂ awal.ÃÂ PopulasiÃÂ danÃÂ sampelÃÂ padaÃÂ penelitianÃÂ iniÃÂ adalahÃÂ siswaÃÂ tingkatÃÂ XIÃÂ TMOÃÂ 1ÃÂ danÃÂ siswaÃÂ tingkatÃÂ XIÃÂ TMOÃÂ 2ÃÂ tahunÃÂ diklatÃÂ 2008/2009.ÃÂ DataÃÂ diambilÃÂ dariÃÂ tesÃÂ kemampuanÃÂ awalÃÂ siswaÃÂ untukÃÂ mengetahuiÃÂ bahwaÃÂ keduaÃÂ sampelÃÂ berdistribusiÃÂ normal.ÃÂ DataÃÂ diujiÃÂ normalitas,ÃÂ homogenitasÃÂ danÃÂ ujiÃÂ tÃÂ (ujiÃÂ hipotesis).ÃÂ HasilÃÂ analisisÃÂ statistikÃÂ menunjukkanÃÂ adanyaÃÂ perbedaanÃÂ signifikan.ÃÂ RataÃ¢â¬ÂrataÃÂ prestasiÃÂ siswaÃÂ tingkatÃÂ XIÃÂ TMO2ÃÂ sebesarÃÂ 78,81ÃÂ danÃÂ lebihÃÂ ting daripadaÃÂ siswaÃÂ tingÃ¢â¬ÂkatÃÂ XIÃÂ TMO1ÃÂ denganÃÂ rataÃ¢â¬ÂrataÃÂ 74,83.ÃÂ KataÃÂ kunci:ÃÂ wiringÃÂ diagram,ÃÂ meja,ÃÂ sistemÃÂ pemanasanÃÂ awalÃÂ ÃÂ TheÃÂ aimÃÂ ofÃÂ thisÃÂ researchÃÂ isÃÂ toÃÂ findÃÂ outÃÂ theÃÂ differenceÃÂ betweenÃÂ maintenanceÃÂ andÃÂ ÃÂ repairÃÂ competenceÃÂ ofÃÂ dieselÃÂ engineÃÂ fuelÃÂ systemÃÂ inÃÂ eleventhÃÂ gradersÃÂ atÃÂ SMKÃÂ IslamÃÂ PemalangÃÂ trainingÃÂ yearÃÂ 2008/2009ÃÂ usingÃÂ twoÃÂ differentÃÂ learningÃÂ mediums.ÃÂ TheyÃÂ areÃÂ tableÃÂ andÃÂ wiringÃÂ diagramÃÂ ofÃÂ preheatingÃÂ system.ÃÂ TheÃÂ populationÃÂ andÃÂ sampleÃÂ ofÃÂ theÃÂ reserachÃÂ wereÃÂ eleventhÃÂ gradersÃÂ ofÃÂ TMOÃÂ 1ÃÂ andÃÂ TMOÃÂ 2ÃÂ trainingÃÂ yearÃÂ 2008/2009.ÃÂ DataÃÂ wasÃÂ takenÃÂ fromÃÂ studentÃ¢â¬â¢ÃÂ firstÃÂ abilityÃÂ toÃÂ identifyÃÂ thatÃÂ bothÃÂ samplesÃÂ hadÃÂ normalÃÂ distributions.ÃÂ TheÃÂ dataÃÂ wasÃÂ thenÃÂ testedÃÂ inÃÂ accordanceÃÂ withÃÂ itsÃÂ normality,ÃÂ homogeneity,ÃÂ andÃÂ tÃ¢â¬ÂtestÃÂ (hypothesisÃÂ test).ÃÂ TheÃÂ statisticalÃÂ analysisÃÂ resultÃÂ indicatesÃÂ thatÃÂ thereÃÂ isÃÂ significantÃÂ difference.ÃÂ TheÃÂ averageÃÂ studentsÃ¢â¬â¢ÃÂ achievementÃÂ ofÃÂ eleventhÃÂ gradersÃÂ ofÃÂ TMOÃÂ 2ÃÂ isÃÂ 78,81ÃÂ andÃÂ itÃÂ isÃÂ higherÃÂ thanÃÂ eleventhÃÂ gradersÃÂ ofÃÂ TMOÃÂ 1ÃÂ withÃÂ theÃÂ averageÃÂ 74,83. ÃÂ Keywords:ÃÂ wiringÃÂ diagram,ÃÂ table,ÃÂ preheatingÃÂ system